Complex Liver Resections for Colorectal Metastases: Are They Safe in the Low-Volume, Resource-Poor Caribbean Setting? - Shamir O. Cawich; Dexter A. W. Thomas; Chunilal Ramjit; Roderick Bhagan; Vijay Naraynsingh (Case Reports in Surgery)
Introduction. Although many authorities suggest that major liver resections should only be carried out in high-volume specialized centres, many patients in the Caribbean do not have access to these health care systems. Presentation of a Case. A 50-year-old woman with a solitary colorectal metastasis invading the inferior vena cava underwent an extended left hepatectomy with caval resection and reconstruction. Several technical maneuvers were utilized that were suited to the resource-poor environment. Conclusion. We suggest that good outcomes can still be attained in the resource-poor, low-volume centres once dedicated and appropriately trained teams are available.